Evaluación de un emulsificador de grasa en el comportamiento productivo de pollos de carne en el cantón Balsas, provincia de El Oro. - Asanza Palacios, Carlos Andrés (2017)
The use of additives in broiler rations that allow the release of nutritional principles to improve yields, such as emulsifiers that improve the absorption of fat without affecting animal welfare and consumer health. The present study was carried out in Canton Balsas Province of El Oro. Different levels of emulsifier were evaluated, using 1200 chickens from the Cobb 500 line, divided into four treatments and three replicates. With a completely randomized design, the following treatments were evaluated: T1 (emulsifier 500g / TM) where 75% of palm oil was replaced with emulsifier (By-pass grease); the T2 (emulsifier 1000g / TM) was replaced by 50% of the palm oil by the fat by pass; to T3 (emulsifier 1500g / T), 25% of palm oil was replaced by fat by pass, T4 (control) received the non-fat by pass. ration, consisting of 100 chickens per experimental unit. The study lasted 49 days. The results obtained: greater weight increase was obtained treatment three with 3248 g; the highest food intake treatment three with 5820 g; the best food conversion reached the treatment two with 1.77; the lowest mortality was that of T2 with 1%, in terms of profitability T2 was the most profitable with 15.19%; the pigmentation in T2, T3, T4 was 9.0 based on the range of Roche colors; the lowest amount of abdominal fat 41g and the largest amount in T1 60g. It is concluded that emulsifier can be added at 1000 g / t, replacing up to 50% of palm oil with significant effects on yield, quality of the carcass and economic benefit. Key words: Palm oil, emulsifier, fat by pass.